2012
DOI: 10.1128/aac.00508-12
|View full text |Cite
|
Sign up to set email alerts
|

MBX-500, a Hybrid Antibiotic with In Vitro and In Vivo Efficacy against Toxigenic Clostridium difficile

Abstract: f Clostridium difficile infection (CDI) causes moderate to severe disease, resulting in diarrhea and pseudomembranous colitis. CDI is difficult to treat due to production of inflammation-inducing toxins, resistance development, and high probability of recurrence. Only two antibiotics are approved for the treatment of CDI, and the pipeline for therapeutic agents contains few new drugs. MBX-500 is a hybrid antibacterial, composed of an anilinouracil DNA polymerase inhibitor linked to a fluoroquinolone DNA gyrase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…In our hands, the antigerminant CamSA has lower efficacy in protecting hamsters from C. difficile strain 630, compared to mice; this finding is not unexpected. Previous reports have consistently shown that CDI treatment in hamsters results in worse outcomes than in a corresponding mouse model (36)(37)(38)(39). Furthermore, treatment efficacy is dependent on the C. difficile strain used in the hamster model (40).…”
Section: Discussionmentioning
confidence: 98%
“…In our hands, the antigerminant CamSA has lower efficacy in protecting hamsters from C. difficile strain 630, compared to mice; this finding is not unexpected. Previous reports have consistently shown that CDI treatment in hamsters results in worse outcomes than in a corresponding mouse model (36)(37)(38)(39). Furthermore, treatment efficacy is dependent on the C. difficile strain used in the hamster model (40).…”
Section: Discussionmentioning
confidence: 98%
“…The MTD approach is also being used to combat the development of resistance to antimicrobials. MBX-500 has been designed as a hybrid of two classes of antibiotics, fluoroquinolone and anilinouracil, for the treatment of Clostridium difficile infections (Butler et al, 2012 ). TD-1792, a cephalosporin-vancomycin hybrid, has passed a phase II clinical trial for gram-positive skin infections (Stryjewski et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The narrow spectrum of fidaxomicin is believed to contribute to its favourable characteristics in treating recurrent CDI, 89 but the effect of kibdelomycin on recurrent disease has not been investigated yet. MBX-500 also had little activity against most Gram-negative anaerobes, and was selectively active against C. difficile strains among Gram-positive anaerobes 75 . MBX-500 was shown to be efficacious in a gnotobiotic piglet model of acute CDI, with a 100% survival rate and only mild CDI symptoms 99 .…”
Section: Challenges In Developing Novel Antimicrobials Targeting Replmentioning
confidence: 99%
“…MBX-500 was shown to be efficacious in a gnotobiotic piglet model of acute CDI, with a 100% survival rate and only mild CDI symptoms 99 . Though the efficacy of MBX-500 was comparable to that of vancomycin in a hamster model of CDI, it was superior in a murine model of recurrent CDI and associated with improved weight gain in both animal models 75 . The weight gain of infected animals treated with MBX-500 and the results in the murine model suggest that this compound might have a low impact on the gut microbiota.…”
Section: Challenges In Developing Novel Antimicrobials Targeting Replmentioning
confidence: 99%